Green transformation of CO2 to ethanol using water and sunlight by the combined effect of naturally abundant red phosphorus and Bi2MoO6 - Das, Risov; Das, Kousik; Ray, Bitan; Vinod, Chathakudath P.; Peter, Sebastian C. (Energy & Environmental Science, 2022)
Direct photocatalytic conversion of CO2 to ethanol remains a scientific challenge because of the sluggish kinetics of C-C coupling and complex multielectron transfer processes. To achieve a green transformation of CO2 to C1+ products using naturally abundant sunlight and water requires the smart design of an efficient catalyst by selecting the right combination of atoms either in elemental or in compound form. Herein, we report a composite photocatalyst composed of earth abundant red phosphorus (RP) in nano-sheet morphology decorated with Bi2MoO6 nano-particles. The composite synthesised by a facile ultrasonication method produces 51.8 mu mol g(-1) h(-1) of ethanol from CO2. The ability of RP for the conversion of CO2 to C1 has been altered by the introduction of Bi2MoO6. In situ Diffuse Reflectance Infrared Fourier Transform Spectroscopy (DRIFTS) and Kinetic Isotopic Effect (KIE) analysis shed light on the mechanistic pathway, which propose that the presence of Bi-Mo dual sites play a crucial role in the C-C coupling toward the formation of ethanol. Spectroscopic evidence and isotope labeling experiments suggest that the intermediate OCH3* is the key active species for ethanol formation via self-coupling followed by proton transfer.

Influence of support textural property on CO2 to methane activity of Ni/ SiO2 catalysts - Cherevotan, Arjun; Ray, Bitan; Churipard, Sathyapal R.; Kaur, Komalpreet; Gautam, Ujjal K.; Vinod, Chathakudath P.; Peter, Sebastian C. (Applied Catalysis B-Environmental, 2022)
In this work, we elucidated the role of physicochemical textural properties of inert support on the catalyst ac-tivity by impregnating Ni on ordered mesoporous silica (SBA-15 and MCM-41) and non-mesoporous silica (nMPS). The catalyst Ni/SBA-15 exhibited the best CO2 conversion (83%) and product selectivity (99.9 %) followed by Ni/MCM-41 and the least by Ni/nMPS. The difference in the nature of the catalyst, degree of nanoparticle distribution and nanoparticle encapsulation by different silica support were studied by N2 adsorption-desorption and X-ray photoelectron spectroscopy (XPS) experiments. The Operando Diffused Reflec-tance Infrared Fourier Transform Spectroscopy were used to understand the variance in reaction pathway which is accredited to the textural properties of the support. The SBA-15 supported Ni catalyst followed dissociative CO pathway while MCM-41 and nMPS reacted through associative formate mechanism as major pathway. These findings provide a novel perspective on CO2 hydrogenation over Ni-silica, allowing us to tune both activity and selectivity.
Keywords: CO2 methanation; DRIFTS; Mesoporous silica support; Textural properties

Tuning the hybridization and charge polarization in metal nanoparticles dispersed over Schiff base functionalized SBA-15 enhances CO2 capture and conversion to formic acid - Cherevotan, Arjun; Ray, Bitan; Yadav, Anish; Bagchi, Debabrata; Singh, Ashutosh Kumar; Riyaz, Mohd; Churipard, Sathyapal R.; Naral, Vinay; Kaur, Komalpreet; Gautam, Ujjal K.; Vinod, Chathakudath P.; Peter, Sebastian C. (Journal of Materials Chemistry A, 2022)
Different Schiff base functionalized SBA-15 materials were synthesized through condensation reactions between 3-aminopropyltriethoxysilane (APTES) and different aldehydes (glutaraldehyde and butyraldehyde) over a mesoporous silica, SBA-15 (APTES-GLU/SBA-15 and APTES-BUT/SBA-15). Both static and dynamic experiments have been used for testing the CO2 capture efficiency of these materials. The hybridization of the N atom in APTES has been tuned from sp(3) to sp(2) upon condensation facilitating optimum CO2 capture in the direct synthesis of APTES-GLU/SBA-15. The undesirable oxides of nitrogen have been removed during the synthesis process to improve the CO2 capture efficiency. These materials were employed as supports for Pd-Ag and Pd-Ni bimetallic systems for the selective conversion of the captured CO2 to formic acid (FA) in 0.5 M KHCO3 solution. The Pd-Ni catalyst system exhibited enhanced CO2 to FA conversion activity compared to other heterogeneous systems, which is similar to 4 times better than that of the Pd-Ag system in this study. The X-ray absorption studies over the catalyst material confirmed that the relatively electron-deficient Ni in Pd-Ni compared to Ag in Pd-Ag favoured higher charge polarization between the metals in the Pd-Ni system enhancing the CO2 to FA conversion. The experimental observations are well supported by the DFT calculations.